Early Detection Of Acute Myocardial Infarction Using The Dempster Shafer Method - Tarunosudirjo, Rahardian; Purwanti, Endah; Oktaviano, Yudi Her (Indonesian Applied Physics Letters, 2020)
This study aims to design an android application to detect indications of Acute Myocardial Infarction (AMI) using the Dempster Shafer method. The system is built with initial symptoms input parameters and risk factor indicated by AMI. The system output consists of 2 classes, namely AMI and non-AMI. The test results obtained system accuracy of 98%.